Peran Guru PAI Dalam Meningkatkan Kompetensi Pembelajaran PAI di SMP IT Ibnu Qoyyim Kabupaten Boneu - Amrullah, Erik; Nur Widiastuti; Etika Pujianti (UNISAN JURNAL, 2025)
This study aims to analyze the role of Islamic Education (PAI) teachers in improving the learning competence of Islamic Education at SMP IT Ibnu Qayyim, Bone Regency. The learning competencies discussed include pedagogical, professional, social, and personal aspects, which are essential for the success of education based on Islamic values. This research employs a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving PAI teachers, the school principal, and students. Data analysis was conducted using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The results indicate that PAI teachers play a strategic role in enhancing learning competence through several efforts: (1) developing lesson plans that are character-based and contextualized with Islamic values; (2) implementing active and collaborative learning methods such as discussions, religious projects, and daily worship practices; (3) conducting continuous evaluations that assess cognitive, affective, and psychomotor domains; and (4) serving as moral exemplars and motivators who nurture students’ religious spirit in the school environment. Supporting factors for this role include the principal’s support, a strong religious school culture, and parental involvement, while inhibiting factors stem from limited time, learning facilities, and diverse student backgrounds. The findings emphasize that improving Islamic Education learning competence depends not only on methodological mastery but also on the integrity and exemplary behavior of PAI teachers in applying Islamic values in daily practice. Therefore, PAI teachers are expected to continuously enhance their professionalism through training, self-reflection, and innovative teaching approaches aligned with current educational developments while remaining grounded in Islamic principles.